Whole exome sequencing identifies multiple novel candidate genes in familial gastroschisis - Víctor M. Salinas‐Torres; Hugo L. Gallardo‐Blanco; Rafael A. Salinas‐Torres; Ricardo M. Cerda‐Flores; José J. Lugo‐Trampe; Daniel Z. Villarreal‐Martínez; Marisol Ibarra‐Ramírez; Laura E. Martínez de Villarreal (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Genetic association studies for gastroschisis have highlighted several candidate variants. However, genetic basis in gastroschisis from noninvestigated heritable factors could provide new insights into the human biology for this birth defect. We aim to identify novel gastroschisis susceptibility variants by employing whole exome sequencing (WES) in a Mexican family with recurrence of gastroschisis. Methods We employed WES in two affected half‐sisters with gastroschisis, mother, and father of the proband. Additionally, functional bioinformatics analysis was based on SVS–PhoRank and Ensembl–Variant Effect Predictor. The latter assessed the potentially deleterious effects (high, moderate, low, or modifier impact) from exome variants based on SIFT, PolyPhen, dbNSFP, Condel, LoFtool, MaxEntScan, and BLOSUM62 algorithms. The analysis was based on the Human Genome annotation, GRCh37/hg19. Candidate genes were prioritized and manually curated based on significant phenotypic relevance (SVS–PhoRank) and functional properties (Ensembl–Variant Effect Predictor). Functional enrichment analysis was performed using ToppGene Suite, including a manual curation of significant Gene Ontology (GO) biological processes from functional similarity analysis of candidate genes. Results No single gene‐disrupting variant was identified. Instead, 428 heterozygous variations were identified for which SPATA17, PDE4DIP, CFAP65, ALPP, ZNF717, OR4C3, MAP2K3, TLR8, and UBE2NL were predicted as high impact in both cases, mother, and father of the proband. PLOD1, COL6A3, FGFRL1, HHIP, SGCD, RAPGEF1, PKD1, ZFHX3, BCAS3, EVPL, CEACAM5, and KLK14 were segregated among both cases and mother. Multiple interacting background modifiers may regulate gastroschisis susceptibility. These candidate genes highlight a role for development of blood vessel, circulatory system, muscle structure, epithelium, and epidermis, regulation of cell junction assembly, biological/cell adhesion, detection/response to endogenous stimulus, regulation of cytokine biosynthetic process, response to growth factor, postreplication repair/protein K63‐linked ubiquitination, protein‐containing complex assembly, and regulation of transcription DNA‐templated. Conclusion Considering the likely gene‐disrupting prediction results and similar biological pattern of mechanisms, we propose a joint “multifactorial model” in gastroschisis pathogenesis.